Pengaruh Riffles dan Kemiringan Underflow Sluice Box Terhadap Optimalisasi Pemisahan Bijih Timah Skala Laboratorium - Indra Chang; Janiar Pitulima; Guskarnali Guskarnali (MINERAL, 2019)
Underflow sluice box is a mineral processing tool that aims to separate the main minerals from associated minerals based on the principle of gravity concentration, which is equipped with boil boxes and underflow riffles as a separation medium in tin ore. The use of laboratory scale underflow sluice box provides Sn concentrate results with high Sn grade and recovery through the influence of underflow riffles and slope positions. Where underflow riffles parameters are in the position of 0.5 cm, 1 cm and 1.5 cm and the slope used is 0 °, 3 ° and 5 °, the experiment is carried out 9 times using 2 kg feed and the same Sn grade in each sample. From the results of the experiment obtained the dry weight and Sn grade concentrates which were analyzed by Sn grade using Grain Counting Analysis (GCA) and recovery calculations. After analysis and calculation, the highest Sn grade was found in sample 9 with underflow riffles position of 1.5 cm, slope of 5 ° and water flow velocity in the water flow velocity at 54 l/minute at 44.61 %, while recovery was highest in sample 3 with underflow riffles 1.5 cm, slope of 0 ° and water flow velocity in the water discharge at 54 l/minute at 99.13 %. Based on these results it can be said that if the underflow riffles and slope position is greater, the recovery and Sn grade concentrates are obtained high and if the underflow riffles and slope positions are smaller, the recovery is high with a low Sn grade concentrates.